DEN-DY (Dental Diary) AS AN EFFORT TO IMPROVE KNOWLEDGE AND BRUSHING SKILLS IN ELEMENTARY SCHOOL CHILDREN - Dandy Dandy; Fahrur Reza. FA; Dyah Saffana Arsinta; Sitti Aminah; Cut Lieddya Rahmita; Salsabila Shafiya Sugiharto; Afifah Ayestina Pelingga; Endah Aryati Eko Ningtyas; Supriyana Supriyana; Bambang Sutomo (Wealth Community Empowerment, 2025)
This report discusses community service through the media "DEN-DY (Dental Diary)" which aims to improve knowledge and brushing skills in elementary school children in MI Miftahul Huda Suwawal Timur. Dental and oral health is an important aspect of general health, and children often lack adequate education about dental care. Through the development of interesting and interactive educational media, this research aims to overcome the problem of low knowledge and brushing skills among students. The methods used include counseling, distribution of DEN-DY media, and evaluation of results through pretest and posttest. The results showed a significant improvement in students' knowledge and skills after the intervention. It is hoped that this innovation can be a model for dental health programs in other schools.